Opportunities for behavioral rescue under rapid environmental change. (4th July 2019) - Fey, Samuel B.; Vasseur, David A.; Alujević, Karla; Kroeker, Kristy J.; Logan, Michael L.; O'Connor, Mary I.; Rudolf, Volker H. W.; DeLong, John P.; Peacor, Scott; Selden, Rebecca L.; Sih, Andy; Clusella‐Trullas, Susana
Abstract: Laboratory measurements of physiological and demographic tolerances are important in understanding the impact of climate change on species diversity; however, it has been recognized that forecasts based solely on these laboratory estimates overestimate risk by omitting the capacity for species to utilize microclimatic variation via behavioral adjustments in activity patterns or habitat choice. The complex, and often context‐dependent nature, of microclimate utilization has been an impediment to the advancement of general predictive models. Here, we overcome this impediment and estimate the potential impact of warming on the fitness of ectotherms using a benefit/cost trade‐off derived from the simple and broadly documented thermal performance curve and a generalized cost function. Our framework reveals that, for certain environments, the cost of behavioral thermoregulation can be reduced as warming occurs, enabling behavioral buffering (e.g., the capacity for behavior to ameliorate detrimental impacts) and "behavioral rescue" from extinction in extreme cases. By applying our framework to operative temperature and physiological data collected at an extremely fine spatial scale in an African lizard, we show that new behavioral opportunities may emerge. Finally, we explore large‐scale geographic differences in the impact of behavior on climate‐impact projections using a global dataset of 38 insect species. These multiple lines of inference indicate that understanding the existing relationship between thermal characteristics (e.g., spatial configuration, spatial heterogeneity, and modal temperature) is essential for improving estimates of extinction risk. Abstract : Forecasts of species diversity amidst climate change based solely on laboratory measurements of physiological and demographic tolerance likely overestimate risk by omitting the capacity for species to utilize microclimatic variation. The complex nature of microclimate utilization has been an impediment to the advancement of general predictive models. Here, we overcome this impediment and estimate the potential impact of warming on the fitness of ectotherms using a benefit/cost tradeoff derived from the simple and broadly documented thermal performance curve and a generalized cost function. Our framework allows estimating the capacity for "behavioral rescue" to occur in response to climate change.